ANALISIS FAKTOR YANG MEMPENGARUHI PENGGUNAAN MINUMAN BERALKOHOL DIKALANGAN REMAJA - Ade Fristy Syahara; Nurhadi Nurhadi; Abdul Rahman (Jurusan Sosiologi FISIP UNIB, 2020)
The occurrence of increased use of alcoholic beverages in Indonesia. The high use of alcoholic beverages among adolescents is one of the causes of increased use of beverages in Indonesia annually. In 2007 the use of alcoholic beverages among adolescents amounted to 4.9% and a rate of 23% in 2014. This means that as many as 14.4 million Indonesian teenagers are alcoholic beverage users. Therefore, this study aims to understand the causes of alcoholic beverages among adolescents and how the teenagers are using alcoholic beverages. Research is done with qualitative methods by applying in-depth interviews to some informant, observation and document studies. From the research that has been done, it is known that the use of alcoholic beverages is influenced by factors that are inside and outside the individual and the environment have the most important role in the formation of adolescent drinking habits. The use of alcohol at the elementary school level is due to the influence of residential environment while the junior-senior high school level is influenced by social environment. The use of alcoholic beverages is then a ritual that is always done when the youth are gathered and become fleeting shortly when reality is not in accordance with expectationsThe occurrence of increased use of alcoholic beverages in Indonesia. The high use of alcoholic beverages among adolescents is one of the causes of increased use of beverages in Indonesia annually. In 2007 the use of alcoholic beverages among adolescents amounted to 4.9% and a rate of 23% in 2014. This means that as many as 14.4 million Indonesian teenagers are alcoholic beverage users. Therefore, this study aims to understand the causes of alcoholic beverages among adolescents and how the teenagers are using alcoholic beverages. Research is done with qualitative methods by applying in-depth interviews to some informant, observation and document studies. From the research that has been done, it is known that the use of alcoholic beverages is influenced by factors that are inside and outside the individual and the environment have the most important role in the formation of adolescent drinking habits. The use of alcohol at the elementary school level is due to the influence of residential environment while the junior-senior high school level is influenced by social environment. The use of alcoholic beverages is then a ritual that is always done when the youth are gathered and become fleeting shortly when reality is not in accordance with expectations Keywords: Juvenile delinquency, Alcohol consumption, Alcohol abuse, Adolescent association, Deviant behavior.